The coverage rates for influenza vaccination and related factors in Korean adults aged 50 and older with chronic disease: based on 2016 Community Health Survey data - Kyeong Hyang Byeon; Jaiyong Kim; Boyoung Choi; Bo Youl Choi (Epidemiology and Health, 2018)
OBJECTIVES This study aims to identify the coverage rates for influenza vaccination and related factors depending on chronic disease in Korean adults aged 50 and older. METHODS The 2016 Korea Community Health Survey was used for analysis. Chi-square test was performed to investigate the coverage rates for influenza vaccination depending on chronic disease, and a multiple logistic regression analysis was used to identify the factors associated with influenza vaccination, by chronic disease. RESULTS In men with ≥1 chronic disease, 39.8% of 50-64 years of age, and 86.8% of elderly (over 65 years of age) received influenza vaccination. In women with ≥1 chronic disease, 58.7% of 50-64 years of age, and 89.9% of elderly (over 65 years of age) received influenza vaccination (p<0.001). The chronic diseases associated with influenza vaccination were hypertension (odds ratio [OR], 1.27; 95% confidence interval [CI], 1.19 to 1.37), diabetes (OR, 1.41; 95% CI, 1.28 to 1.55) in men aged 50-64, hypertension (OR, 1.34; 95% CI, 1.20 to 1.49), diabetes (OR, 1.17; 95% CI, 1.02 to 1.33), chronic cardiovascular disease (OR, 1.31; 95% CI, 1.07 to 1.60) in elderly (over 65 years of age). In women aged 50-64, hypertension (OR, 1.39; 95% CI, 1.30 to 1.49), diabetes (OR, 1.51; 95% CI, 1.35 to 1.68), chronic cardiovascular disease (OR, 1.31; 95% CI, 1.05 to 1.64), and hypertension (OR, 1.55; 95% CI, 1.40 to 1.71), diabetes (OR, 1.27; 95% CI, 1.12 to 1.43) in elderly (over 65 years of age). CONCLUSIONS Populations in aged 50-64 are recommendation subject for vaccination or classified as high-risk group in case with chronic disease. Though subject over 60 years old is age close to the elderly, the coverage rates for vaccination was low. It is necessary to devise strategies to raise the coverage rates for vaccination.